(untitled) (Research, Society and Development, 2020)
In coturniculture nutrition is the factor that most burdens production costs, thus studies with the use of foods alternative to corn and soybean meal, has grown considerably throughout Brazil, due to the great potential of agroindustry production of parents who generates numerous co-products or by-products that have sufficient nutritional quality to be placed in the rations without interfering with the performance or quality of the final product, making it possible to reduce the polluting potential of these co-products when discarded inappropriately. In this context, the aim of this review is to address some alternative foods that are used in the feeding of cutting quails, as well as their effects on zootechnical performance in the different stages of breeding of these birds and also their effects on the quality of the final product. To perform this review, an analysis of scientific studies that used alternative foods in diets of quail was made, showing their effects. It can be concluded that various alternative foods such as acerola residue, licuri bagasse, guava meal, crambe meal, passion fruit residue, cashew nut meal, soybean husk and fodder palm meal can be used to feed meat-type quails, assisting in the reduction of diet costs without influence on the zootechnical characteristics.